2022
DOI: 10.1186/s12893-022-01843-1
|View full text |Cite
|
Sign up to set email alerts
|

Comparisons of outcomes of open surgery versus endovascular intervention for thrombotic popliteal artery aneurysm with acute lower limb ischemia: a systematic review

Abstract: Background Thrombotic popliteal artery aneurysm (PAA) with acute lower limb ischemia (ALI) is a serious disease leading to amputation. The choice of emergency procedures is not clearly defined, and the difference in therapeutic efficiency between open surgery and endovascular intervention is still unclear. Method We conducted a comprehensive search through PubMed, Wiley Online Library and ScienceDirect. According to the predefined inclusion and exc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 46 publications
0
0
0
Order By: Relevance
“…In fact, a metanalysis by Xiao et al including 32 papers on thrombosed PAA highlighted an overall technical success rate of 90.73% without any significant difference between the open surgery and endovascular intervention groups, while the primary patency rate and the limb salvage rate at 1-year follow-up was significantly lower in the open group, when compared to the endovascular route [13].…”
Section: Discussionmentioning
confidence: 99%
“…In fact, a metanalysis by Xiao et al including 32 papers on thrombosed PAA highlighted an overall technical success rate of 90.73% without any significant difference between the open surgery and endovascular intervention groups, while the primary patency rate and the limb salvage rate at 1-year follow-up was significantly lower in the open group, when compared to the endovascular route [13].…”
Section: Discussionmentioning
confidence: 99%
“…Arterial injury following TKA has traditionally been managed through open surgery, however, recent studies showed promising results with endovascular strategies. Endovascular treatment has the advantage of avoiding general anesthetics with less local morbidity than open surgery [ 7 , 24 , 27 , 28 ]. The type of endoscopic intervention depends on the type of arterial injury.…”
Section: Discussionmentioning
confidence: 99%